IMPLEMENTASI METODE ROLE MODEL SEBAGAI UPAYA UNTUK MENUMBUHKAN SIKAP KARAKTERISTIK KEDISIPLIN DALAM PEMBELAJARAN PENDIDIKAN AGAMA DI MAN 8 JOMBANG - Hidayat , M. Dani; Masruroh, Laily (EL-Islam, 2025)
Abstract: Success in teaching and learning is a highly expected outcome for teachers. However, to achieve a conducive and efficient learning environment, an appropriate teaching method or model is necessary. The issue focus of this research is the implementation of the role model method to enhance students' disciplinary traits within Islamic education, aiming to develop character aligned with Islamic principles. The research findings reveal that Islamic education teachers adopt strategic approaches to apply the role model method effectively and foster student discipline during the process of learning.The use of approach strategy towards students can maximize the results of implementing the role model method through religious activities such as congregational prayer, reading the Quran, reading Asmaul Husna, etc.